Neuropeptide FF and prolactin‐releasing peptide decrease cortical excitability through activation of NPFF receptors. (12th February 2015) - Buffel, Ine; Meurs, Alfred; Portelli, Jeanelle; Raedt, Robrecht; De Herdt, Veerle; Sioncke, Lynn; Wadman, Wytse; Bihel, Frederic; Schmitt, Martine; Vonck, Kristl; Bourguignon, Jean‐Jacques; Simonin, Frederic; et al.
Summary: Objective: Drugs with a novel mechanism of action are needed to reduce the number of people with epilepsy that are refractory to treatment. Increasing attention is paid to neuropeptide systems and several anticonvulsant neuropeptides have already been described, such as galanin, ghrelin, and neuropeptide Y (NPY). Many others, however, have not been investigated for their ability to affect epileptic seizures. In this study, the potential anticonvulsant activities of three members of the RF‐amide neuropeptide family, neuropeptide FF (NPFF), prolactin‐releasing peptide (PrRP), and kisspeptin (Kp) and other receptor ligands (NPFF1/2 R, GPR10, and GRP54, respectively) were tested in the motor cortex stimulation model. Methods: A train of pulses with increasing intensity (0–10 mA over 150 s, 50 Hz, pulse width 2 msec) was delivered to the motor cortex of rats. The threshold intensity for eliciting a motor response (i.e., motor threshold) was determined through behavioral observation and used as a measure for cortical excitability. The threshold was determined before, during, and after the intracerebroventricular (i.c.v.) administration of various NPFF1/2 R, GPR10, and GPR54 receptor ligands. Results: NPFF and PrRP significantly increased the motor threshold by a maximum of 143 ± 27 and 83 ± 13 μA, respectively, for the doses of 1 nmol/h (p < 0.05). The increase of motor threshold by NPFF and PrRP was prevented by pretreatment and co‐treatment with the NPFF1/2 R antagonist RF9. Pretreatment with a selective NPFF1 R antagonist also prevented the threshold increase induced by NPFF. Kp did not increase motor threshold. Significance: Intracerebroventricular infusion of NPFF or PrRP decreases cortical excitability in rats through activation of NPFFRs. Furthermore, the NPFF1 R is required for the NPFF‐induced decrease in cortical excitability.